Reversible exchange of wetting state of a hydrophobic surface via phase change material coating. Issue 2 (3rd January 2018) - Yilbas, Bekir Sami; Ali, Haider; Al-Sharafi, Abdullah; Al-Aqeeli, Nasser
Abstract : Reversible exchange of the wetting state of a hydrophobic surface is examined. Abstract : Reversible exchange of the wetting state of a hydrophobic surface is examined. Solution crystallization of a polycarbonate surface is carried out to form hierarchically distributed micro/nano size spherules and fibrils on the surface. Although the solution crystallized surface has hydrophobic characteristics, the contact angle hysteresis remains high. Functionalized silica particles are deposited on the crystallized polycarbonate surface to improve the droplet contact angle and lower contact angle hysteresis. The liquid film of n -octadecane with 1.5 μm thickness is formed on the functionalized silica particles deposited crystallized surface, which results in hydrophilic surface characteristics. The n -octadecane film solidifies upon reducing the temperature on the surface and solid flakes of n -octadecane are formed. This arrangement changes the surface wetting state to hydrophobic. Liquefaction and solidifying of the n -octadecane film at the functionalized silica deposited surface gives rise to reversible exchange of surface wetting state. This behavior is attributed to exposure of emerging functionalized silica particles to the free surface in the region of the solid n -octadecane flakes. The water droplet is cloaked by the liquid n -octadecane while forming a ridge around the droplet. In this case, the water droplet becomes mobile at the surface because flow develops in the n -octadecane liquid film at the onset of liquefaction.